A Study on Correlations Between Computer Literacy and Attitudes Toward Internet Use Among Generation Y: A Malaysian Perspective - Pathmananathan, P. Ravindran; Aseh, Khairi; Kenny, Kamal (Archives of Business Research, 2021)
There are over a few hundred thousand daily internet users with the ease with which businesses are now able to cash in on the internet and reach a huge market of consumers Online banking, mobile banking, and other business transactions all have seen a great deal of advancement due to modern technology. It appears that young people are increasingly using the internet instead of watching TV. Many have debated how computer literacy affects their online shopping. This research aims to discover the correlation between computer literacy and internet usage among those born in the 1980s Purchasing behaviour has a link to attitude, economic factors, tend to encourage people in Klang Valley, Malaysia. This was performed with a set method in place.